Small cell carcinoma of the ovary with hypercalcemia: Case report and review of the literature - A, Gerday; E, Marbaix; JL, Squifflet; F, Mazzeo; M, Luyckx (Clinical Journal of Obstetrics and Gynecology, 2018)
We describe here the case of a 23-year old woman with small cell carcinoma of the ovary of the hypercalcemic type (SCCOHT) with SMARC-A4 mutation who benefited from surgery in two steps leading to a total hysterectomy with bilateral salpingo-oophorectomy, omentectomy, pelvic and lombo-aortic lymph nodes dissection. She also received 6 courses of poly-chemotherapy after the surgery. A close follow-up was then performed by clinical examination every three months with determination of serum calcium and CA125 level as well as imaging with thoraco-abdominal CT scan. To date, the patient has a disease-free survival of more than 9 years. We also reviewed the literature on this topic and discuted the new diagnostic and prognostic genetic tool SMARC-A4 mutation.